Universal Access to a Quality Education: Research and Recommendations for the Elimination of Curricular Stratification - Carol Corbett Burris; Jennifer Weiser Bezoza; Kevin G. Welner (Great Lakes Center for Education Research and Practice, 2009)
This policy brief makes the case for schools across the country to put an end to policies that cast off students into unchallenging, low-track classrooms. The authors recommend a clear process for the phasing out of curricular stratification in grades K-10, beginning with the lowest track and granting meaningful access to AP and IB courses to all students. The brief includes model statutory language to implement its recommendations.